The heritage of traditional Malay literature a historical survey of genres, writings and literary views - Braginskiĭ, V. I. (Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde, 2004)
This book, the first comprehensive survey of traditional Malay literature in English since 1939, embraces more than a millennium of Malay letters from the vague data of the seventh century up to the early beginnings of the modern literatures in the late nineteenth century. The long path trodden by traditional Malay literature is viewed in historical and theoretical perspectives as a development of integral system, caused by cultural and religious changes, primarily by gradual Islamization. This changing system considered in the entirety of its genres and works, is seen both externally and internally: from the point of view of modern scholarship and through the examination of indigenous concepts of literary creativity, poetics and aesthetics.